PERSEPSI SISWA KELAS IX SMP MUHAMMADIYAH 1 PEKANBARU TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SECARA DARING DI MASA PANDEMI - Maulana Ihsan; Ni Putu Nita Wijayanti; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is about student’s perceptions of online sport and health physical education learning. This research is a descriptive research with a quantitative descriptive approach. The method used is a survey with a questionnaire instrument. The purpose of this research was to determine student’s perceptions of online sport and health physical education subject during the pandemic. The population in this research were students of class IX, amounting to 150 people. The sampling technique is purpotional random sampling, which is as many as 30 students. Based on the description of the results of the research on the technical indicators of 30 students, there were 10 students or 33.33% in the good category, and in the very good category there were 5 students or 16.67%. Thus the perception of students is good. In the indicators of the learning process, there are 16 students in the poor category or 53.33%. Thus the perception of students is not good. In the support indicator, there are 14 students in the good category or 46.67%. Thus the perception of students is good.Key Words: Student Perception, Online Learning, Physical Education, Pandemic